The queen of the damned - Rice, Anne, 1941-2021 (Rice, Anne, 1941-2021. Vampire chronicles, 1988)
Intertwines the stories of rock star and vampire Lestat, beautiful twins haunted by a gruesome tragedy, and Akasha, mother of all vampires, who dreams of godhood.